2001
DOI: 10.1038/sj.tpj.6500067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of psoriasis disease-associated genes through pharmacogenomic expression profiling

Abstract: Psoriasis is recognized as the most common T cell-mediated inflammatory disease in humans. Genetic linkage to as many as six distinct disease loci has been established but the molecular etiology and genetics remain unknown. To begin to identify psoriasis disease-related genes and construct in vivo pathways of the inflammatory process, a genome-wide expression screen of multiple psoriasis patients was undertaken. A comprehensive list of 159 genes that define psoriasis in molecular terms was generated; numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
144
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 43 publications
17
144
0
1
Order By: Relevance
“…These data suggest that IL-22 might be one of the primary soluble factors that link the adaptive immune response with KCs and innate immunity in the pathophysiology of psoriasis. Expression studies of psoriatic vs normal or uninvolved skin have identified altered expression of Ͼ1300 genes in psoriatic lesions (38,48,49). We demonstrated here that the genes regulated by IL-20 subfamily cytokines were highly correlated with genes modified in psoriatic skin, further supporting their potential roles in the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These data suggest that IL-22 might be one of the primary soluble factors that link the adaptive immune response with KCs and innate immunity in the pathophysiology of psoriasis. Expression studies of psoriatic vs normal or uninvolved skin have identified altered expression of Ͼ1300 genes in psoriatic lesions (38,48,49). We demonstrated here that the genes regulated by IL-20 subfamily cytokines were highly correlated with genes modified in psoriatic skin, further supporting their potential roles in the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 68%
“…Proteins of this family, whose genes are found in the epidermal differentiation complex, are calcium-binding proteins that are associated with inflammation, some of which have been shown to have chemotactic and direct antimicrobial activities (51)(52)(53). Other genes induced by the IL-20 subfamily cytokines and also in psoriatic skin include chemokines, angiogenic factors, tissue kallikreins, and ␤-defensins (38,48,49,71). Chemokines and angiogenic factors might further enhance proinflammatory responses through a positive feedback loop by recruiting additional leukocytes and promoting angiogenesis in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…T cells found in psoriasis lesions are strongly biased as type 1 T cells, with CD4 ϩ ͞Th1 cells predominant in the dermis of lesions and CD8 ϩ ͞Tc1 cells predominant in the epidermis (8). We have proposed a type 1 inflammatory pathway to explain the pathogenesis and maintenance of psoriasis (9), based on the genomic fingerprint of skin lesions (10)(11)(12). Potentially, the type 1 pathway is regulated in diseased skin by increased production of IL-23, which is a product of infiltrating myeloid DCs (13).…”
mentioning
confidence: 99%
“…Though various microarray studies, beginning with Oestreicher et al (2001), have been employed in hopes of detecting disease genes for psoriasis, the gaps in the disease mechanism still exist. In particular, we have not yet understood the initiators, as well as the overall mechanism of the disease.…”
Section: Introductionmentioning
confidence: 99%